Lesser prairie-chicken reproductive success, habitat selection, and response to trees - Lautenbach, Joseph Mark (Kansas State University, 2014)
The lesser prairie-chicken (Tympanuchus pallidicinctus) is a species of prairie grouse native to the southwest Great Plains. Population declines and threats to populations of lesser prairie-chickens led U.S. Fish and Wildlife Service to list the species as “threatened” under the protection of the Endangered Species Act in May 2014. Lesser prairie-chickens are found within three distinct ecoregions of Kansas and Colorado and portions of the species’ range are affected by tree encroachment into grasslands. The effect of trees on lesser prairie-chickens is poorly understood. I evaluated habitat selection and reproductive success and across the northern portion of the species’ range. I captured female lesser prairie-chickens within the three different ecoregions in Kansas and Colorado to track nest and brood survival and measure nest and brood habitat. My findings show that there are regional and annual variations in nest and brood survival. Mean nest survival during 2013 and 2014 was estimated to be 0.388 (95% CI = 0.343 – 0.433) for a 35-day exposure period. Brood survival during 2013 and 2014 was estimated to be 0.316 (95% CI = 0.184 – 0.457) for 56 days. Chick survival was the lowest during the first week of life and is probably a limiting factor for population growth. Chick and brood survival decreased as Julian hatch date increased. Across the northern portion of the species’ range, females consistently select visual obstruction between 2-3 dm. Vegetation at the nest changes between regions and years to reflect environmental and regional conditions. Broods consistently selected habitats with greater percent cover of forbs than was expected at random across all study sites. Broods also selected against areas of bare ground. The threshold of lesser prairie-chicken use was 2 trees/ha throughout the year. No nests were located within areas with greater densities. Lesser prairie-chickens had a greater probability of use at greater distances from trees and at lower tree densities. To provide adequate nesting habitat managers should provide 2-3 dm of visual obstruction. Providing forb cover with visual obstruction between 2.5-5 dm near nesting habitat should provide adequate habitat for broods. Removing trees in core habitats and expand removal efforts outward should expand potential habitat for lesser prairie-chickens.
Keywords: Lesser Prairie-Chicken; Tympanuchus pallidicinctus; Nest survival; Brood ecology; Trees; Kansas; Colorado; Habitat; Ecology; Biology (0306); Wildlife Conservation (0284); Wildlife Management (0286)